Impact of corneal donor lens status on two-year course and outcome of Descemet membrane endothelial keratoplasty (DMEK) - Schaub, Friederike; Pohl, Layla; Enders, Philip; Adler, Werner; Bachmann, Bjorn O.; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2017)
PURPOSE: Our purpose was to investigate the impact of lens status of corneal donors on the two-year course and clinical outcome of Descemet membrane endothelial keratoplasty (DMEK). METHODS: In 181 DMEK surgeries, 136 phakic and 45 pseudophakic donor corneas were grafted. In this retrospective audit we compared the lens status of corneal donors regarding the outcome measures best spectacle-corrected visual acuity (BSCVA), central corneal thickness (CCT), and endothelial cell density (ECD) at 1, 3, 6, 12, and 24 months, as well as intra- and postoperative complication rates and graft detachment rates requiring re-bubbling. RESULTS: Comparing the use of phakic and pseudophakic donor tissue in DMEK surgery, BSCVA results revealed no significant differences during the two-year course (p ≥ 0.087). CCT showed significantly lower values at 1 month (553.8 ± 56 vs. 625.2 ± 119 μm; p < 0.001) and 6 months follow-up (530.6 ± 49.9 vs. 557.3 ± 47 μm; p = 0.026) for phakic donor tissue recipients, but were comparable later (p ≥ 0.173). ECD values were statistically higher 6 (1915 ± 390 vs. 1565 ± 420 cells/mm2; p < 0.001) and 24 months postoperatively (1772 ± 384 vs. 1375 ± 377 cells/mm2; p = 0.030) in phakic donor tissue recipients. Mixed regression analyses demonstrated a significant association between ECD results and donor lens status (p = 0.029) and donor ECD (p = 0.028), but donor age did not show significant influence (p = 0.241). CONCLUSION: ECD is higher in phakic corneal donors and appears to remain at a higher level during the course resulting in initially faster reduction of corneal edema compared to pseudophakic DMEK grafts. Nevertheless, pseudophakic transplants with high ECD seem to produce comparable functional results in recipients after a two year course.
EVALuna2:34171